2017
DOI: 10.1021/acsami.7b12308
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Cell–Chip Coupling by Rapid Femtosecond Laser Patterning of Soft PEDOT:PSS Biointerfaces

Abstract: Interfacing soft materials with biological systems holds considerable promise for both biosensors and recording live cells. However, the interface between cells and organic substrates is not well studied, despite its crucial role in the effectiveness of the device. Furthermore, well-known cell adhesion enhancers, such as microgrooves, have not been implemented on these surfaces. Here, we present a nanoscale characterization of the cell-substrate interface for 3D laser-patterned organic electrodes by combining … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
36
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 26 publications
(37 citation statements)
references
References 30 publications
(57 reference statements)
1
36
0
Order By: Relevance
“…[32][33][34][35][36] When implemented in a three-terminal architecture as an NVRM, PEDOT:PSS devices show exceptionally low switching energies (10 pJ for a 100 µm 2 device) in addition to linear and symmetric conductance response required for "blind" weight update (i.e., not involving a read). [15] These features combined with materials compatibility for 3D stacking [37] and biological interfacing [38,39] make organic neuromorphic devices very promising for integration in hardware-based ANN. [15] These features combined with materials compatibility for 3D stacking [37] and biological interfacing [38,39] make organic neuromorphic devices very promising for integration in hardware-based ANN.…”
Section: Introductionmentioning
confidence: 99%
“…[32][33][34][35][36] When implemented in a three-terminal architecture as an NVRM, PEDOT:PSS devices show exceptionally low switching energies (10 pJ for a 100 µm 2 device) in addition to linear and symmetric conductance response required for "blind" weight update (i.e., not involving a read). [15] These features combined with materials compatibility for 3D stacking [37] and biological interfacing [38,39] make organic neuromorphic devices very promising for integration in hardware-based ANN. [15] These features combined with materials compatibility for 3D stacking [37] and biological interfacing [38,39] make organic neuromorphic devices very promising for integration in hardware-based ANN.…”
Section: Introductionmentioning
confidence: 99%
“…To extend this capability further, we produce centimetre long fibres to guide cellular alignment, where the fibre can simultaneously function as an impedimetric sensor detecting dynamics of cell coverage (Fig.4 D). Cell coverage on PEDOT:PSS electrode surfaces is known to increase the electrode's sensing impedance (41,42). Coupled with simultaneous live cell imaging permitted by the fibre array, it is found that in our fibre-electrode setup, the impedance increases most noticeably during the initial stages of cell attachment and fibre-guided cell alignment (within approximatively 100 min from cell sedimentation).…”
Section: Inflight Fluidic Fibre Printingmentioning
confidence: 73%
“…5D). Cell coverage on PEDOT:PSS electrode surfaces is known to increase the electrode's sensing impedance (42). Coupled with simultaneous live-cell imaging permitted by the transparency of the fiber array, it is found that in our fiber-electrode setup, the impedance increases most noticeably during the initial stages of cell attachment and fiber-guided cell alignment (within approximatively 100 min from cell sedimentation).…”
Section: Pedot:pss Fiber-based Biointerface Devicesmentioning
confidence: 76%